Asymmetric Synthesis of Two Analogues of Meiogynin A. Issue 11 (20th February 2013) - Dardenne, Jérémy; Desrat, Sandy; Guéritte, Françoise; Roussi, Fanny
Abstract: The efficient and asymmetric synthesis of two analogues of meiogynin A, a natural sesquiterpenoid dimer that was recently isolated by our group, is reported. The key reaction was a highly selective intermolecular Diels–Alder reaction between an aromatic triene and two chiral dienes. This convergent synthesis maximizes the atom economy concept, as the expected compounds were obtained in only eight steps without any protecting groups. Abstract : Two analogues of meiogynin A, a natural sesquiterpenoid dimer that interacts with a family of antiapoptotic proteins, were synthesized. They were obtained in only eight steps with very good selectivity, without any protection steps.